Skyrmion Lattice Phases in Thin Film Multilayer. (3rd September 2020) - Zázvorka, Jakub; Dittrich, Florian; Ge, Yuqing; Kerber, Nico; Raab, Klaus; Winkler, Thomas; Litzius, Kai; Veis, Martin; Virnau, Peter; Kläui, Mathias
Abstract: Phases of matter are ubiquitous with everyday examples including solids and liquids. In reduced dimensions, particular phases, such as the 2D hexatic phase and corresponding phase transitions occur. A particularly exciting example of 2D ordered systems are skyrmion lattices, where in contrast to previously studied 2D colloid systems, the skyrmion size and density can be tuned by temperature and magnetic fields. This allows for the system to be driven from a liquid phase to the onset of a hexatic phase as deduced from the analysis of the hexagonal order. Using coarse‐grained molecular dynamics simulations of soft disks, the skyrmion interaction potentials are determined, and it is found that the simulations are able to reproduce the phase behavior. This shows that not only the static behavior of skyrmions is qualitatively well described in terms of a simple 2D model system but skyrmion lattices are versatile and tunable 2D model systems that allow for studying phases and phase transitions in reduced dimensions. Abstract : Skyrmion lattices are shown to be promising playgrounds to study 2D phase transitions. While investigating phases with respect to skyrmion density, the hexatic phase emerges, demonstrating the 2D nature of the multilayer system. Concluding from comparison with simulations, skyrmion lattices act as a 2D model system with advantages in terms of tenability and speed over existing systems like colloids.